2022
DOI: 10.1155/2022/5491038
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Immune and Inflammation Characteristics of Atherosclerosis from Different Sample Sources

Abstract: Background. Atherosclerosis is the predominant cause of cardiovascular diseases. Existing studies suggest that the development of atherosclerosis is closely related to inflammation and immunity, but whether there are differences and similarities between atherosclerosis occurring at different sites is still unknown. We elucidated the pathological characteristics of peripheral vascular diseases by using bioinformatic analyses on immune cells and inflammation-related gene expression in atherosclerotic arteries an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Patients with atherosclerosis, compared with control individuals, have a higher level of inflammatory biomarkers such as C-reactive protein (CRP) and interleukin-1β (IL-1β) [ 11 , 12 ]. Through analyzing atherosclerotic plaques, abundant infiltrated immune cells and increased expression of inflammatory mediators are identified [ 13 ]. Besides, imaging techniques have enabled the characterization of arterial inflammation in CAD patients and atherosclerotic animal models [ 14 , 15 ].…”
Section: Inflammation In Coronary Artery Diseasementioning
confidence: 99%
“…Patients with atherosclerosis, compared with control individuals, have a higher level of inflammatory biomarkers such as C-reactive protein (CRP) and interleukin-1β (IL-1β) [ 11 , 12 ]. Through analyzing atherosclerotic plaques, abundant infiltrated immune cells and increased expression of inflammatory mediators are identified [ 13 ]. Besides, imaging techniques have enabled the characterization of arterial inflammation in CAD patients and atherosclerotic animal models [ 14 , 15 ].…”
Section: Inflammation In Coronary Artery Diseasementioning
confidence: 99%
“…We identified the top 10 hub genes based on degree value by using Cytoscape software, including PTPRC, TYROBP, TNF, ITGAM, SPI1, LCP2, CSF1R, CCR5, and ITGAX. Nie reported that PTPRC was considered to be an immune marker gene in atherosclerosis development [ 22 ]. Liu reported that the upregulated TYROBP was identified as a common hub gene and as an immune-responsive hub gene in the advanced atherosclerotic plaques [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathological studies of atherosclerotic plaques have shown abundance of immune cells in addition to the deposited lipids. 15 Foam cell and fatty steak formation are the two earliest steps in atherosclerotic plaque progression. Foam cells are lipid laden macrophages which have engulfed oxidised LDL particles.…”
Section: Inflammation In Various Phases Of Atherosclerosismentioning
confidence: 99%